Performance Enhancement of Solar Stills with Novel Materials: A Concise Review - Ahmed Alhamzawi (Journal of Heat and Mass Transfer Research)
According to the severe global warming and increasing demand for freshwater worldwide, different sustainable solutions for supplying water have been considered. Solar desalination is a promising method to convert saline and brackish water resources to distilled water. Solar stills are one of the simple solar desalination methods and have low costs compared to similar solar-powered methods. However, the low distillation capacity and vast distillation area requirements present a challenge for further development of this technique. The application of novel materials that enhance the heat and mass transfer rate in solar stills can be a suitable approach for performance enhancement. In the current review, the most recent advancements according to the novel materials that enhance the distillation rate of the solar stills will be discussed and reviewed concisely. The investigated novel materials in the current review includes different types of natural materials that have been proposed by researchers. Finally, concluding points and future study suggestions will be presented to the researchers. The current review provides the researchers with the most recent advances in the integration of novel materials with conventional solar stills for heat and mass transfer enhancement.